Improved Sperm Count and Motility in Young Men Surgically Treated for Cryptorchidism in the First Year of Life - Feyles, Francesca; Peiretti, Valentina; Mussa, Alessandro; Manenti, Marco; Canavese, Ferdinando; Cortese, Maria Grazia; Lala, Roberto (European Journal of Pediatric Surgery, 2014)
Introduction The timing of surgery in cryptorchidism has been debated for a long time. Reports on histology suggest better fertility outcomes with early surgery, whereas evidence of long-term improved fertility still lacks sound data. The aim of this study is to analyze sperm count and motility in a cohort of young men operated on during the first 2 years of life for cryptorchidism.Patients and Methods A total of 78 young men (age, 18–26 years) surgically treated for cryptorchidism in the second year of life were recalled to evaluate testicular volume and sperm count and motility. Of the 78 young men, 51 accepted to participate to clinical and sperm evaluation. Relationship between total sperm count (TSC), sperm motility (SM), and age at surgery was investigated by Student t-test and Fisher test. Patients were divided into two groups: those patients who were submitted to surgery in their first year of life (Group A) and those patients who were submitted to surgery in their first and the second year of life (Group B). We investigated the ratio of those patients with normal sperm count to those patients with abnormal sperm count (we defined as normal TSC > 15 million and SM > 15%) and compared the mean TSC and SM in the two groups.Results TSC were slightly but not significantly higher in the first group (45.5 ± 15.5 million/mL vs. 36.5 ± 23.6 million/mL, p = 0.107) and SM (30.5% ± 11.3% vs. 26.5% ± 15.4%, p = 0.341). The percentage of patients with normal sperm count and motility were significantly higher in the first group: normal TSC was found in 26 of 27 patients (96.3%) in Group A versus 18 of 24 patients (75.0%) in Group B (p = 0.042), normal SM was found in 26 of 27 patients (96.3%) versus 16 of 24 patients (66.7%), respectively (p = 0.008). In the two groups, no statistically significant difference was found neither in the proportion of patients with bilateral cryptorchidism, in the position of the testes, nor in the ratio of subjects treated with hormonal therapy before being operated on.Conclusions In formerly cryptorchid subjects submitted to surgery in the first 2 years of life, the percentage of patients with normal sperm count and motility is higher than 95%, with even better fertility prognosis if orchiopexy is performed in the first year of life.
Keywords: cryptorchidism; orchiopexy; sperm analysis; testicular volume